Learning Videos Based on Problem-Based Learning (PBL) to Improve Students’ Ability in Writing Indonesian Procedural Texts in Grade IV Elementary School - Kadek Gantha Gangga Kusuma; Maria Goreti Rini Kristiantari; Basilius Redan Werang (Jurnal Media dan Teknologi Pendidikan, 2025)
Indonesian language learning is still dominated by conventional methods that are less effective in improving students’ comprehension, particularly in procedural text material. The lack of engaging instructional media results in low student participation. One solution is using Problem-Based Learning (PBL)-based instructional videos to help students understand concepts through problem-solving. This study aims to develop and evaluate the feasibility and effectiveness of PBL-based instructional videos. This research follows a Research and Development (R&D) approach using the ADDIE model. The subjects included three experts (content, instructional design, and media) and 22 fourth-grade students in individual and small-group trials. Data were collected through expert validation, student response questionnaires, and learning outcome tests. Data analysis included validity testing with descriptive quantitative analysis, prerequisite testing with chi-square normality tests, and effectiveness testing with a one-sample t-test. Validation results indicate the media is highly feasible, with scores above 90%, while effectiveness tests showed tvalue (1.879) > ttable (1.720), proving significant improvement in student comprehension. In conclusion, PBL-based instructional videos are feasible and effective in enhancing students' understanding, with school and teacher support for implementation. This study implies the need for school and teacher support to optimize media implementation for more effective and engaging learning.